Percepción de la Calidad de Vida de los Miembros de la Mesa de Participación Efectiva de la Localidad de Sumapaz (2022)
Understanding the perception of the victims of the armed conflict regarding their quality of life being a topic of social interest, which gives rise to this investigation with which it is intended to know and analyze the psychological and social components of this population. From the subjective framework of the concept "quality of life" from the perspectives of each individual